PENGARUH WAKTU PENUAAN TIRUAN TERHADAP KEKERASAN PADUAN Al-10Si-3Cu - Muhammad Syahid; Hairul Arsyad; Abdul Fatah Rozali (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
Al-Si alloy is one of the alloys that are widely used in the industry because it has a good cast and good strength. To increase its mechanical strength Cu alloy can be added which can be covered. Al-10Si-Cu alloy is one of the alloys commonly used in industry, especially the automotive industry because it has excellent mechanical strength. This research is focused on looking at the effect of artificial aging on T6 heat treatment to increase the hardness of Al-10Si-3Cu alloy results from casting. Dilution behavior was carried out at a temperature of 520 oC for 2 hours then quenched in water and then performed artificial aging carried out at 130oC with aging time varying from 5 minutes to 120 hours. Material characterization carried out hardness testing, tensile test, microstructure observation with an optical microscope. The highest hardness was obtained with an 80 hour holding time of 86.05 BHN where CuAl2 precipitates underwent optimum conditions. The most upper tensile strength was collected at 80 hours holding time, namely 335.063 MPa with strain value 1.133%. A low strain value indicates that this condition has begun to overgrow, so embryo has started to occur. Keywords: heat treatment, aluminum, Al-10Si, artificial aging Keywords: heat treatment, aluminum, Al - 10Si, artificial aging